Gaining a Past, Losing a Future: Web 2.0 and Internet Historicity - Allen, Matthew (University of Queensland, School of English, Media Studies & Art History, 2012)
This article explore how, in the first decade of the twenty-first century, the internet became historicised, meaning that its public existence is now explicitly framed through a narrative that locates the current internet in relation to a past internet. Up until this time, in popular culture, the internet had been understood mainly as the future-in-the-present, as if it had no past. The internet might have had a history, but it had no historicity. That has changed because of Web 2.0, and the effects of Tim O’Reilly’s creative marketing of that label. Web 2.0, in this sense not a technology or practice but the marker of a discourse of historical interpretation dependent on versions, created for us a second version of the web, different from(and yet connected to) that of the 1990s. This historicising moment aligned the past and future in ways suitable to those who might control or manage the present. And while Web 3.0, implied or real, suggests the ‘future’, it also marks out a loss of other times, or the possibility of alterity understood through temporality.